DETERMINING TYPES OF CONSCIOUS CONSUMERS WHO PREFER NUTRITION LABELING - Tóth, Ildikó; Szakály , Zoltán (Applied Studies in Agribusiness and Commerce, 2025)
One of the most important pillars of a healthy lifestyle is healthy nutritional value, in which FOP nutrition labels can support consumers in making the right decision. A healthy diet is essential for overall well-being and the prevention of many chronic diseases. Special attention must be paid to the use of FOP nutrition values in order to prevention and healthy decision-making. It is important that people can interpret the nutritional value of food as simply as possible, which FOP nutrition labels can help them with. The packaging has to provide realistic and accurate information about the product. This study describes four types of FOP nutrition labels used in the European Union: Nordic Keyhole, Nutri-Score, Traffic Lights, Nutrinform Battery. During the conducted focus group interviews, the participants got acquainted with these nutrition labels and created the personality types that they can imagine knowing and using the given FOP nutrition label.